2022
DOI: 10.3390/cryst12030415
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence Properties of Ho2O3-Doped Y2O3 Stabilized ZrO2 Single Crystals

Abstract: Single crystals of Ho2O3-doped Y2O3 stabilized ZrO2 (YSZ) with different Y2O3 and Ho2O3 contents were grown by the optical floating zone method. XRD and Raman spectra were measured and showed that crystal samples all had tetragonal structures. Measurements of positron annihilation lifetime spectra indicated that the increase in Y2O3 concentration led to the increases of defects and mean positron lifetime, which enhanced the scattering of light and reduced the luminous intensity and the quantum yield (QY) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Previous studies have demonstrated that the presence of defects may likewise affect the optical absorption of the crystal. [20][21][22] In this article, the effects of ion implantation of Co ions on the electronic structure and optical properties of cubic ZrO 2 are investigated by a combination of ion implantation experiments and simulations, aiming to discuss the contribution of Co ions as well as oxygen vacancy defects to the visible light absorption properties of cubic ZrO 2 .…”
Section: Doi: 101002/pssb202300227mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the presence of defects may likewise affect the optical absorption of the crystal. [20][21][22] In this article, the effects of ion implantation of Co ions on the electronic structure and optical properties of cubic ZrO 2 are investigated by a combination of ion implantation experiments and simulations, aiming to discuss the contribution of Co ions as well as oxygen vacancy defects to the visible light absorption properties of cubic ZrO 2 .…”
Section: Doi: 101002/pssb202300227mentioning
confidence: 99%
“…Previous studies have demonstrated that the presence of defects may likewise affect the optical absorption of the crystal. [ 20–22 ]…”
Section: Introductionmentioning
confidence: 99%
“…The second (τ2) and third (τ3) components are longer than the first component (τ1); therefore, τ2 and τ3 could be related to the flicker light emitted by excitons associated with antisite defects in the matrix [51]. The average decay time of the sample is then defined by (6) [49]: The fluorescence lifetimes for the 4 G5/2 → 6 H7/2 emission peak from YGG: Sm 3+ and YAG: Sm 3+ single crystals were then calculated to be 0.705 ms and 0.466 ms, respectively (Table 4). Thus, the fluorescence lifetime of YGG: Sm 3+ is not only longer than that of the YAG: Sm 3+ crystal, but it is also longer than those of CaGdAlO4: Sm 3+ (0.69 ms) and NaGd(MnO4): Sm 3+ crystals (0.5574 ms) [18,52,53]; this is probably the consequence of the greater intensity of its 4 G5/2 → 6 H7/2 emission peak, which allows for a greater participation of Sm 3+ ions in this transition and results in a longer fluorescence lifetime [54,55].…”
Section: Fluorescence Lifetime Measurementsmentioning
confidence: 99%
“…Rare-earth-based luminescent materials have been widely studied for their excellent spectral properties, which include a high and adjustable luminescence, long fluorescence lifetime, and large Stokes shift [1,2]. Consequently, they have extensive uses in lightemitting diodes (LEDs), lasers, optical temperature sensors, optical communications, display panels, luminescence dosimeters, and biomedical diagnostics [3][4][5][6]. Nevertheless, considerable efforts are still being employed to improve the luminescence properties of such rare-earth-doped materials [7][8][9], and the color, intensity, and luminescence efficiency have been shown to strongly depend on the structure and composition of the luminescent center [8,10].…”
Section: Introductionmentioning
confidence: 99%